Kewenangan Bertindak (Recht Bevoegdheid) Lembaga Perkreditan Desa (LPD) Sebagai Pemegang Hak Tanggungan - Ida Bagus abhimantara (Notaire, 2022)
AbstractIn order to accommodate the needs of the village community, Governor’s Decree Number 972 of 1984 concerning the Establishment of a Village Credit Institution in the Province of Bali which became the forerunner to the birth of the Village Credit Institutions (LPD) in Bali Province to accommodate the financial management of the village community, which in carrying out its activities only serves community in the local village area. The efforts carried out by the LPD cannot be separated from the legal constructions of the agreement and are subject to the existing laws and regulations, therefore the LPD must emphasize its position and position in acting legally in order to obtain legal certainty and legal protection in carrying out of law actions related to credit distribution and guarantees. The LPD provisions regulated in the Bali Provincial Regulation Number 3 of 2017 concerning Village Credit Institutions (LPD) cannot be classified as legal entities and the LPD’s position as the holder of mortgage rights is not appropriate and does not have the authority to act (bevoegheid) and this has implications for the LPD’s executorial rights in carrying out their duties. execution of the object of the guarantee and in the case of the purchase of the collateral the LPD is also not a legal subject who has the right to purchase either part or all of the collateral.Keywords: Village Credit Institutions (LPD); Mortgage Rights; Authority to Act. AbstrakDemi mengakomodir kebutuhan desa pakraman, Surat Keputusan (SK) Gubernur Nomor 972 Tahun 1984 tentang Pendirian Lembaga Perkreditan Desa di Provinsi Daerah Tingkat I Bali yang menjadi cikal bakal lahirnya LPD di Provinsi Bali untuk mengakomodir pengelolaan keuangan masyarakat desa pakraman, yang dalam menjalankan kegiatannya hanya melayani masyarakat di wilayah desa pakraman setempat. Usaha-usaha yang dijalankan LPD tersebut tidak terlepas dari konstruksi-konstruksi hukum perjanjian dan tunduk pada peraturan perundang-undangan yang ada, maka dari itu LPD harus mempertegas posisi dan kedudukannya dalam bertindak secara hukum agar mendapat kepastian hukum dan perlindungan hukum dalam melakukan perbuatan-perbuatan hukum terkait penyaluran kredit dan penjaminannya. Ketentuan LPD yang diatur dalam Peraturan Daerah Provinsi Bali Nomor 3 Tahun 2017 tentang Lembaga Perkreditan Desa tidak dapat diklasifikasikan sebagai badan hukum dan kedudukan LPD selaku pemegang hak tanggungan tidaklah tepat serta tidak memiliki kewenangan bertindak (bevoegheid) dan hal tersebut berimplikasi terhadap hak eksekutorial LPD dalam melakukan eksekusi atas objek jaminannya dan dalam hal pembelian agunannya LPD juga bukan subjek hukum yang berhak melakukan pembelian baik sebagian ataupun seluruh agunannya.Kata Kunci: Lembaga Perkreditan Desa (LPD); Hak Tanggungan; Kewenangan Bertindak.